2002
DOI: 10.1111/1467-8276.00363
|View full text |Cite
|
Sign up to set email alerts
|

Partial Market Liberalization and the Efficiency of Policy Reform: The Case of the European Dairy Sector

Abstract: This article analyzes the efficiency of partial market liberalization and policy reform with an application to the European dairy sector. In a second best world, partial moves toward market liberalization are not always efficiency improving. We develop a general equilibrium model to investigate the efficiency implications of discrete changes in government policy. The analysis covers price and quantity instruments used in both domestic and trade policy. We derive simple conditions under which partial market lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“… Bouamra‐Mechemache et al (2002) modeled the EU price support system. The difference is that the European policy clearly acts as a price support system in that government purchases can be sold into the international markets at lower prices than in the domestic market.…”
mentioning
confidence: 99%
“… Bouamra‐Mechemache et al (2002) modeled the EU price support system. The difference is that the European policy clearly acts as a price support system in that government purchases can be sold into the international markets at lower prices than in the domestic market.…”
mentioning
confidence: 99%
“…Another limitation of this analysis is that we are simulating the effects of a single policy measure Bouamra-Mechemache et al (2002). found that partial market liberalization is not necessarily welfare enhancing in a second-best world with multiple interrelated policies.14 This value is calculated as the discounted sum of the equilibrium rental value over the duration of the quota regime (until 2015, so far).…”
mentioning
confidence: 99%
“…We also consider domestic production quotas q yi restricting the production of the ith producer. The introduction of domestic production quotas is relevant, as they can affect the distortionary effects of trade policy (e.g., Bouamra-Mechemache et al, 2002). Again, for simplicity, we focus our analysis on output quotas, with q yi !…”
Section: Policy Distortions and Market Equilibriummentioning
confidence: 99%
“…This would identify secondbest conditions under which partial market liberalization is immiserizing. This is illustrated by Bouamra-Mechemache et al (2002) in an analysis of partial domestic and trade policy reform in the European Union (EU) dairy sector. The EU dairy sector is of interest because, even after the Uruguay round of GATT negotiations and recent EU policy reforms, it is still subject to significant policy distortions: domestic milk production quotas, domestic subsidies, as well as trade barriers (including import quotas and export subsidies).…”
Section: V3 a Special Case: When T* Is Differentiablementioning
confidence: 99%
See 1 more Smart Citation